Workers' Compensation and Occupational Injuries and Illnesses - Ruser, John W. (Journal of Labor Economics, 1991)
A longitudinal establishment data set is used to assess the effect of changes in workers' compensation benefits on the incidence of lost-workday injury and illness cases in manufacturing for the years 1979-84. Higher benefits are found generally to increase lost-workday cases. However, consistent with theory, the benefit effect is smaller in larger, more highly experience-rated establishments. After initial estimates are obtained using ordinary and weighted least squares, several count data models are explored that are more appropriate for the integer injury and illness counts in the data. The results are consistent across the specifications.